Participation and dialogue in development - Neves, David Telles (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
"Participation" is a frequently articulated requirement within the context of community development. Yet despite this, the concept of participation is neither comprehensively theorised, nor entirely unproblematic. The theoretical paucity surrounding participation is particularly marked within accounts of its interactional and relational dynamics . This thesis is accordingly concerned with theorising the interactional and relational features of participation in, and for, development. To this end a small development intervention, constituted as an agricultural co-operative within a rural area of South Africa, is examined. In this inquiry the phenomenon of participation is viewed through the lens of dialogical-activity. This enables explication of the "joint activity" directed towards participatory development, within the focal research setting. The overarching theoretical framework for this thesis is conferred by Activity theory. Orientated towards examining the collective and artefactually mediated nature of human action, Activity theory is foregrounded in Y. Engeström's (1989; 1999b) analytic schema of the Activity System. This Activity System framework is expanded by the inclusion of communicative and semiotic elements; an inclusion effected by reference to R. Engeström's theory of communicative action (1995,1999), which in turn, draws on theoretical precepts gleaned from the work of Mikhail Bakhtin. The resultant fusing of dialogue and activity therefore serves to extend Activity theoretical insights. The results of this research are based on data collected from a multitude of sources within the focal participatory development research setting, including internal project documentation, interview transcripts and field notes. The dialogical Bakhtin-derived an alytic categories of speech genre , voice and social language were drawn on in order to examine this textual data , and to explicate the interactional and relational features of participatory development. Analysis of these served to reveal the polyphony of (speech genre constituted) voices, wherein the phenomenon of participation is disparately accentuated. The results chapter moreover discusses the substantial mismatches and discontinuities in the referential object invoked by the various roleplayers, within the focal research context. This thesis considers the sources of these discontinuities and tensions, including how they point to historically constituted contradictions within participatory development. It furthermore briefly examines the opportunities and affordances these offer up for expansive new forms of activity. Finally, in re-examining participation and development, the complex, and sometimes antithetic relationship that exists between these two concepts and their associated social practices, are considered.
Keywords: Action theory; Communication in economic development